Analisis Korelasi dan Pemetaan Konsentrasi Karbon Dioksida (CO2) Terhadap Suhu Udara di Kabupaten Gresik - Moh. Zulfan Maulidan Wahyu Andriansyah; Siti Zainab (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In Gresik Regency, a district in the East Java Province, industrial activities can impact air quality and human health. A recent study monitored carbon dioxide (CO2) levels and air temperature to understand their relationship. Researchers collected data through direct measurements and utilized the Pearson Correlation method to establish the connection. Additionally, they used the linear regression method to determine the data's mathematical equation. The study found that the carbon dioxide concentration ranged from 438 ppm to 1483 ppm, while the air temperatures fluctuated between 29°C and 34°C. Statistical analysis revealed a correlation of -0.626 between carbon dioxide concentration and air temperature, with the linear regression equation Y=3549.114-95.134X. The results suggest a fairly strong correlation, indicating that the concentration of carbon dioxide influences air temperature. The negative correlation value implies that the relationship between the two variables is contradictory.